A construção do ethos concurseiro: mérito e experiência moral na competição por cargos públicos - Araújo, Henny Nayane Tavares de (2016)
This study aimed to understand how evaluative references related to the concept of individual merit take body and produce normative beliefs through practical experiences, especially the competitive experience of studying for public job selection in Brazil. Through qualitative research based on three types of sources (interviews, approval manuals and online forum), we seek to explore the universe of experience of concurseiros, showing the system of behavioral dispositions and map of perceptions and moral references that is developped in the preparation process for the test. Technical-motivational discurses and narratives of "personal achievement" of concurseiros were analysed, trying to understand how the main elements articulate an ideal of individual self-realization that sustains in itself legitimating criteria of a social hierarchy.